Treatment of obesity-related diabetes: significance of thermogenic adipose tissue and targetable receptors - Pan, Ruping; Liu, Jiadai; Chen, Yong (Frontiers in Pharmacology, 2023)
Diabetes mellitus is mainly subtyped into 4 types according to the pathogenesis, among which, type 2 diabetes mellitus (T2DM) is with highest incidence rate and is most relevant to obesity. It is characterized by high blood glucose, which is primarily due to an insulin resistance in tissues that are responsible for glucose homeostasis (such as liver, skeletal muscle, white adipose tissue [WAT] etc.) combined with an insufficiency of insulin secretion from pancreatic  cells. Treatment of diabetes, especially treatment of diabetic complications (such as diabetic nephropathy) remains problematic. Obesity is one of the main causes of insulin resistance, however, could be potentially intervened by activating A double-blind placebo-controlled study.